(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Enterprise Resource Planning: systems or the ERP systems referto the software packages that integrate all the data and the related processesof an organization into a unified Information System (IS).An ERP system uses acentral database that holds all the data relating to the various systemmodules. In order to achieve a seamless integration, an ERP system usesmultiple hardware and software components. ERP packages are heavily used bylarger in Small and Medium Enterprises. SMEs and implementation of EnterpriseResource Planning (ERP) systems have tended to concentrate on theirdecision-support capabilities rather than their transactional and record-keepingaspects. This paper explores connections between ERP systems and decisionsupport based on the adoption by Small and Medium Enterprises. It offers newinsights into the important objectives are (and should be)the factors influencing an enterprise to adopt ERPand decision-support objectives. Itprovides insights into the decision-support benefits of ERP systems. The studyalso examines relationships between the importance of ERP implementation andits benefits for SMEs.